Efficacy and safety of dronedarone in patients with a prior ablation for atrial fibrillation/flutter: Insights from the ATHENA study. Issue 3 (24th December 2019) - Vamos, Mate; Calkins, Hugh; Kowey, Peter R.; Torp‐Pedersen, Christian T.; Corp dit Genti, Valérie; Wieloch, Mattias; Koren, Andrew; Hohnloser, Stefan H.
Abstract: Background: The role of antiarrhythmic drugs for atrial fibrillation/atrial flutter (AF/AFL) after catheter ablation is not well established. Hypothesis: We hypothesized that changing the myocardial substrate by ablation may alter the responsiveness to dronedarone. Methods: We assessed the efficacy and safety of dronedarone in the treatment of paroxysmal/persistent atrial fibrillation/atrial flutter (AF/AFL) post‐ablation, based on a post hoc analysis of the ATHENA study. A total of 196 patients (dronedarone 90, placebo 106) had an ablation for AF/AFL before study entry. In these patients, the effect of treatment on the first hospitalization because of cardiovascular (CV) events/all‐cause death was assessed, as was AF/AFL recurrence in individuals with sinus rhythm at baseline. The safety of dronedarone vs placebo was also determined. Results: In patients with prior ablation, dronedarone reduced the risk of AF/AFL recurrence (hazard ratio [HR]: 0.65 [95% confidence interval [CI]: 0.42, 1.00]; P < .05) as well as the median time to first AF/AFL recurrence (561 vs 180 days) compared with placebo. The HR for first CV hospitalization/all‐cause death with dronedarone vs placebo was 0.98 (95% CI: 0.62, 1.53; P = .91). Rates of treatment‐emergent adverse events were 83.1% vs 75.5% and rates of serious TEAEs were 27.0% vs 18.9% in the dronedarone and placebo groups, respectively. One death occurred with dronedarone (not treatment‐emergent) and five occurred with placebo. Conclusion: In patients with prior ablation for AF/AFL, dronedarone reduced the risk of AF/AFL recurrence compared with placebo, but not the risk of first CV hospitalization/all‐cause death. Safety outcomes were consistent with those of the overall ATHENA study.